Development and evaluation of a digital education tool for medical students in wound care - Schlupeck, Mischa; Stubner, Birgit; Erfurt-Berge, Cornelia (International Wound Journal, 2020)
The aim of this study was to develop and evaluate an interactive, video-enhanced, and case-based online course for medical students. We chose a case about wound care since this topic is still underrepresented in the medical curriculum. First, instructional videos were created to teach practical skills in wound care. These were implemented into a case-based online course, using the online learning platform ILIAS. In a comparative initial and final survey, numbers of users were assessed, content and structure of the course, as well as the thematic interest of the students and self-assessed gain of competence, were evaluated. Since the summer of 2019, 310 students have successfully completed the course. The survey data showed a high participation rate and a positive response regarding the content as well as the structural concept. Most of the students rated the content within the course as useful for their future medical work (86.1%) and the gain of knowledge superior to a traditional lecture (69.4%). Self-assessments of video-mediated skills showed a significant increase in subjectively perceived competence. The online course is an efficient way to reach many students by the small use of resources. It resembles an option to arouse growing interest in wound care in medical students.
CRIS-Team Scopus Importer:2020-09-25
Keywords: digital education; health care; medical students; practical skills; wound care